Return to Paris: : Thomas Ostermeier and the performatization of the gay identity - Friques, Manoel Silvestre (Revista Brasileira de Estudos da Presença, 2022)
In his productions, the German director Thomas Ostemeier proposes a sociological approach that seeks to present our contemporary age’s social relations and power structures. What are the obstacles to achieving these goals when the focus rests on the intersection of the axes of oppression through race, class and gender? This essay investigates the contradictions inherent in Ostermeier’s self-declared sociological realism, reflecting on the plays Retour à Reims [Return to Reims] (2019) and Histoire de la Violence [History of Violence] (2020), based on the homonymous literary works by Didier Eribon and Édouard Louis, respectively.